Regulation and physiological function of proteins for heat tolerance in cowpea (Vigna unguiculata) genotypes under controlled and field conditions - Selinga, Tonny I.; Maseko, Sipho T.; Gabier, Hawwa; Rafudeen, Mohammed S.; Muasya, A. Muthama; Crespo, Olivier; Ogola, John B. O.; Valentine, Alex J.; Ottosen, Carl-Otto; Rosenqvist, Eva; Chimphango, Samson B. M. (Frontiers in Plant Science, 2022)
The expression of heat shock proteins is considered a central adaptive mechanism to heat stress. This study investigated the expression of heat shock proteins (HSPs) and other stress-protective proteins against heat stress in cowpea genotypes under field (IT-96D-610 and IT-16) and controlled (IT-96D-610) conditions. Plants in the control environment were under 25/20°C (day/night) in a warm chamber and 40/25 °C in a hot chamber. In the field, plants grew at Eensaamheid with 26 to 28°C and at Marapyane with 30 to 32°C monthly average maximum temperatures. Heat stress response analysis of proteins at 72 h in the controlled environment showed 270 differentially regulated proteins identified using label-free quantitative proteomics in IT-96D-610 plants. These plants expressed HSPs and chaperones (BAG family molecular chaperone 6 (BAG6), Multiprotein bridging factor1c (MBF1C) and cold shock domain protein 1 (CSDP1)) in the controlled environment. However, IT-96D-610 plants expressed a wider variety of small HSPs and more HSPs in the field. IT-96D-610 plants also responded to heat stress by exclusively expressing chaperones (DnaJ chaperones, universal stress protein and heat shock binding protein (HSBP)) and non-HSP proteins (Deg1, EGY3, ROS protective proteins, temperature-induced lipocalin and succinic dehydrogenase). Photosynthesis recovery and induction of proteins related to photosynthesis, were better in IT-96D-610 because of the concurrent induction of heat stress response proteins for chaperone functions, protein degradation for repair and ROS scavenging proteins and PSII operating efficiency (Fq’/Fm’) than IT-16. This study contributes to identification of thermotolerance mechanisms in cowpea that can be useful in knowledge-based crop improvement.